Preliminary results of a new approach for three-dimensional reconstruction of Dynamic AngioThermography (DATG) images based on the inversion of heat equation. Issue 9 (September 2016) - Brancaccio, R.; Bettuzzi, M.; Morigi, M.P.; Casali, F.; Levi, G.; Baldazzi, G.; Inferrera, P.
Graphical abstract: Highlights: We fully characterized DATG system (emissivity, response, resolution). We ideated a method to invert heat equation for blood pattern. We developed an algorithm to convert time dependent sequence into three-dimension. We experimentally tested the algorithm on a phantom and on in vivo experiment. We proposed how to carried out improvement of our method for the future. Abstract: Dynamic AngioThermography (DATG) is a contact-plate technique capable of producing a digital representation of breast vascularity. The inception and growth of a tumor are associated with neoangenesis, which may result in a demonstrable alteration in the regional blood flow, while in normal health conditions the vascularity remains unchanged throughout life. DATG, if included in the clinical evaluation for breast cancer, could potentially improve the accuracy of the diagnosis of this disease. Conventional DATG is limited, however, in that it is a projection (i.e. two-dimensional) imaging technique that does not provide any information on the depth and its effect on the pattern of the perfusion revealed by this technique. In fact, the blood pattern is detected by projecting temperature signals on the plate, thus acquiring a digital two-dimensional image. In this article we propose a new approach for extracting information on depth through the inversion of the Fourier heat equation. The idea is to extract the information along the third axis while acquiring and analyzing the temporal sequence during the process of image formation. The method implemented has been tested on a dedicated "electric phantom" and in one in vivo experiment. In spite of the limits of these preliminary tests, the experimental results have shown that this method makes it possible to obtain a 3D representation of the vascularity. Although it appears to be promising, further validation and characterization of our technique are required.